2004
DOI: 10.1007/s11243-004-3224-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, e.p.r., cyclic voltammetric and biological activities of copper(II) complexes with macrocyclic ligands

Abstract: Eight new macrocyclic ligands have been prepared by the reaction of the precursor diketone (benzil, glyoxal, diacetyl or 2,3-pentanedione) with a diamine (thiosemicarbazide or semicarbazide). Copper(II) complexes of these ligands have been synthesized and characterized by elemental analysis, molar conductance, magnetic susceptibility, i.r., u.v.-vis, 1 H-n.m.r., mass and e.p.r. spectral studies. Mass, n.m.r. and i.r. data indicate the condensation of the diamine and diketone and the whole molecular ion structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The values of D q in Co(II) complexes were calculated from transition energy ratio diagram using the Q 3 ./Q 2 ratio [15]. Our results are in agreement with the complexes reported earlier [24,25]. The Nephelauxetic parameter E was readily obtained by usign the relation: E = B (Complex)/B (free ion ), where B (free ion) for Mn(II) is 786 cm -1 , for Co(II) is 1120 cm -1 [26,27].…”
Section: Ligand Field Parameterssupporting
confidence: 90%
“…The values of D q in Co(II) complexes were calculated from transition energy ratio diagram using the Q 3 ./Q 2 ratio [15]. Our results are in agreement with the complexes reported earlier [24,25]. The Nephelauxetic parameter E was readily obtained by usign the relation: E = B (Complex)/B (free ion ), where B (free ion) for Mn(II) is 786 cm -1 , for Co(II) is 1120 cm -1 [26,27].…”
Section: Ligand Field Parameterssupporting
confidence: 90%
“…But the ratio between the anodic and cathodic currents suggests that the process is simple one-electron transfer, quasi-reversible process [36,37]. On comparing the cyclic voltammograms, we observed that the variation in oxidation and reduction potential may be due to distortion in the geometry of the complex which arises due to different anions coordinated to the metal ion [38].…”
Section: Cyclic Voltammetrymentioning
confidence: 86%
“…The band present near 760 cm 21 in thiocarbohydrazide may be assigned to the free n(CvS). This band is also present in all complexes which indicates that sulphur is not coordinated to the metal atom [25,27,28].The absence of bands near 2550 cm 21 (characteristic of a thiol group) rule out the possibility of thione-thiol tautomerism [29]. The C-N stretch occurs in the range 1350-1000 cm 21 .…”
Section: Chemistrymentioning
confidence: 93%